2016
DOI: 10.1021/acs.jmedchem.6b00043
|View full text |Cite
|
Sign up to set email alerts
|

Double Methotrexate-Modified Neuropeptide Y Analogues Express Increased Toxicity and Overcome Drug Resistance in Breast Cancer Cells

Abstract: Bioconjugates containing the neuropeptide Y (NPY) analogue [F(7),P(34)]-NPY as targeting moiety are able to deliver toxic agents specifically to breast cancer cells that overexpress the human Y1-receptor (hY1R). To increase their activity, multiple toxophores can be attached to one peptide. Herein, synthesis and characterization of [F(7),P(34)]-NPY conjugates containing two methotrexate (MTX) molecules are presented. First, carboxytetramethylrhodamine was linked to [F(7),P(34)]-NPY by amide or enzymatic linkag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 36 publications
(94 reference statements)
0
23
0
Order By: Relevance
“…For hY 1 R, a number of selective full‐length ligands with 36 amino acids have been reported, most prominently [Phe 7 ,Pro 34 ]NPY . Since 2001, hY 1 R has been known to be overexpressed in breast tumour tissue, making selective agonists even more relevant for use as shuttles for the site‐specific delivery of cytotoxic drugs . The preference of an agonist over an antagonist for that purpose lies in the ability of the agonist to induce internalisation of the receptor–peptide complex, thereby delivering the conjugated drug into the cell .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For hY 1 R, a number of selective full‐length ligands with 36 amino acids have been reported, most prominently [Phe 7 ,Pro 34 ]NPY . Since 2001, hY 1 R has been known to be overexpressed in breast tumour tissue, making selective agonists even more relevant for use as shuttles for the site‐specific delivery of cytotoxic drugs . The preference of an agonist over an antagonist for that purpose lies in the ability of the agonist to induce internalisation of the receptor–peptide complex, thereby delivering the conjugated drug into the cell .…”
Section: Discussionmentioning
confidence: 99%
“…The preference of an agonist over an antagonist for that purpose lies in the ability of the agonist to induce internalisation of the receptor–peptide complex, thereby delivering the conjugated drug into the cell . For [Phe 7 ,Pro 34 ]NPY, this was already successfully applied by conjugation of cytotoxic tubulysin‐derived peptides or methotrexate, both of which were selectively delivered into hY 1 R‐overexpressing (tumour) cells and induced apoptosis. Another approach was the coupling of carbaborane clusters to agonist peptides to enhance the boron concentration in tumour cells for boron neutron capture therapy .…”
Section: Discussionmentioning
confidence: 99%
“…MTX is the most commonly used disease-modifying anti-rheumatic agent and is also effective at treating patients with breast cancer ( 28 , 29 ). Previous studies have demonstrated that MTX induces greater cytotoxicity and growth inhibition in leukemia and other malignant cell types compared with other treatments ( 30 , 31 ). It has been demonstrated that sustained ERS is a major contributor to MTX-induced cell death, as indicated by the induction of several unfolded protein response markers, which ultimately induce apoptosis ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…A follow‐up study intended to increase the toxicity of the NPY‐based PDC by doubling the amount of toxophores. [ 188 ] Therefore, MTX was simultaneously conjugated to the side‐chains of Lys 4 and the inserted Lys 22 in [F 7 ,P 34 ]‐NPY via GFLG‐linkers, resulting in the double‐modified PDC [K 4 (GFLG‐MTX),F 7 ,K 18 (GFLG‐MTX),P 34 ]‐NPY. A higher cytotoxic effect of the double‐MTX PDC compared to single‐MTX PDCs was obtained on various hY 1 R‐rexpressing breast cancer cell lines.…”
Section: Variation Of the Drug Cargo In Receptor‐targeting Peptide‐drmentioning
confidence: 99%